2013
DOI: 10.1017/s1751731112001875
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and host effects on methanogenesis in the grazing ruminant

Abstract: Concentrations of methane (CH 4 ) in the atmosphere have almost doubled since the mid 1700s, and it is estimated that ,30% of the global warming experienced by the planet in the last century and a half can be attributed to CH 4 . Between 25% and 40% of anthropogenic CH 4 , emissions are estimated to arise from livestock farming. Mitigating absolute emissions from livestock is extremely challenging technically and is made more difficult because of the need to increase food production to meet the demands of a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
2
29
2
1
Order By: Relevance
“…However, over the entire grazing season, NDF and ADF concentrations were lower in E1 than in E2 or E3. Several studies have suggested that level of intake rather than digestibility is the main determinant of absolute CH 4 emissions (DeRamus et al, 2003;Beauchemin and McGinn, 2006;Pinares-Patino et al, 2007;Hart et al, 2009;Pelve et al, 2012;Boland et al, 2013;Clark, 2013).However, the difference in absolute CH 4 emissions between experimental periods in the current work cannot be explained solely by differences in DMI. McCaughey et al (1999) found significant differences in DMI among cattle grazing swards of contrasting quality, but not between sampling periods, while corresponding absolute CH 4 emissions (L/day) differed significantly between sampling periods.…”
mentioning
confidence: 52%
See 3 more Smart Citations
“…However, over the entire grazing season, NDF and ADF concentrations were lower in E1 than in E2 or E3. Several studies have suggested that level of intake rather than digestibility is the main determinant of absolute CH 4 emissions (DeRamus et al, 2003;Beauchemin and McGinn, 2006;Pinares-Patino et al, 2007;Hart et al, 2009;Pelve et al, 2012;Boland et al, 2013;Clark, 2013).However, the difference in absolute CH 4 emissions between experimental periods in the current work cannot be explained solely by differences in DMI. McCaughey et al (1999) found significant differences in DMI among cattle grazing swards of contrasting quality, but not between sampling periods, while corresponding absolute CH 4 emissions (L/day) differed significantly between sampling periods.…”
mentioning
confidence: 52%
“…However, over the entire grazing season, NDF and ADF concentrations were lower in E1 than in E2 or E3. Several studies have suggested that level of intake rather than digestibility is the main determinant of absolute CH 4 emissions (DeRamus et al, 2003;Beauchemin and McGinn, 2006;Pinares-Patino et al, 2007;Hart et al, 2009;Pelve et al, 2012;Boland et al, 2013;Clark, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A range of different strategies are being investigated to reduce methane emissions from farmed ruminants (reviewed by Martin et al, 2010;Buddle et al, 2011;Clark, 2013). Vaccination of ruminants against rumen methanogens has the potential to reduce methane emissions by decreasing the number or activity of methanogens in the rumen.…”
Section: Introductionmentioning
confidence: 99%